Viloxazine versus imipramine in the treatment of enuresis - Yurdakök, Murat; Kınık, Erol; Güvenç, Hüseyin; Bedük, Yaşar (The Turkish Journal of Pediatrics, 1987)
The effectiveness of imipramine and viloxazine was evaluated in 37 children with enuresis. It was shown that both imipramine and viloxazine produced an improvement in the same degree in these subjects. No side effects were reported in the use of both these drugs in the study. It is therefore proposed that viloxazine may be used as an alternative drug instead of imipramine with advantages of potentially no fatal side effects.